Monitoring quality of care in hepatocellular carcinoma: A modified Delphi consensus. Issue 11 (25th September 2022) - Maharaj, Ashika D.; Lubel, John; Lam, Eileen; Clark, Paul J.; Duncan, Oliver; George, Jacob; Jeffrey, Gary P.; Lipton, Lara; Liu, Howard; McCaughan, Geoffrey; Neo, Eu‐Ling; Philip, Jennifer; et al.
Abstract: Although there are several established international guidelines on the management of hepatocellular carcinoma (HCC), there is limited information detailing specific indicators of good quality care. The aim of this study was to develop a core set of quality indicators (QIs) to underpin the management of HCC. We undertook a modified, two‐round, Delphi consensus study comprising a working group and experts involved in the management of HCC as well as consumer representatives. QIs were derived from an extensive review of the literature. The role of the participants was to identify the most important and measurable QIs for inclusion in an HCC clinical quality registry. From an initial 94 QIs, 40 were proposed to the participants. Of these, 23 QIs ultimately met the inclusion criteria and were included in the final set. This included (a) nine related to the initial diagnosis and staging, including timing to diagnosis, required baseline clinical and laboratory assessments, prior surveillance for HCC, diagnostic imaging and pathology, tumor staging, and multidisciplinary care; (b) thirteen related to treatment and management, including role of antiviral therapy, timing to treatment, localized ablation and locoregional therapy, surgery, transplantation, systemic therapy, method of response assessment, and supportive care; and (c) one outcome assessment related to surgical mortality. Conclusion : We identified a core set of nationally agreed measurable QIs for the diagnosis, staging, and management of HCC. The adherence to these best practice QIs may lead to system‐level improvement in quality of care and, ultimately, improvement in patient outcomes, including survival.